Stability Assessment of Multi-Stage Slopes Considering Local Failure - Wu, Haochen; Sun, Miaojun; Wang, Jinnan (Frontiers in Earth Science, 2022)
The analytical method for slope stability analysis requires a collapse mechanism in advance. The collapse mechanism for a multi-staged slope is generally assumed to be overall failure, whereas this kind of slope may suffer from local failure. However, a local failure is rarely reported in the previous research for multi-staged slopes, which may result in an overestimate for slope stability. To this end, local failure is incorporated into the collapse mechanism for the first time, so as to develop a complete approach to assess the stability of multi-stage slopes. The modified pseudo-dynamic method is conducted to properly account for seismic effects. Thanks to the limit analysis method and strength reduction technique, the safety factor of a multi-stage slope is obtained. The result obtained by the presented approach shows a good agreement with that of previous literature and numerical calculations. The collapse mechanism of multi-stage slopes is studied, and the safety factor is presented schematically for a wide range of parameters. The results show that the local failure for a multi-stage slope often manifests under the intense seismic effects.